Phospholipase C‐β1 potentiates glucose‐stimulated insulin secretion. Issue 10 (3rd July 2019) - Hwang, Hyeon-Jeong; Yang, Yong Ryoul; Kim, Hye Yun; Choi, Yoonji; Park, Kyoung-Su; Lee, Ho; Ma, Ji Su; Yamamoto, Masahiro; Kim, Jaeyoon; Chae, Young Chan; Choi, Jang Hyun; Cocco, Lucio; et al.
ABSTRACT: PLC‐β exerts biologic influences through GPCR. GPCRs are involved in regulating glucose‐stimulated insulin secretion (GSIS). Previous studies have suggested that PLC‐βs might play an important role in pancreatic β cells. However, because of a lack of the specific inhibitors of PLC‐β isozymes and appropriate genetic models, the in vivo function of specific PLC‐β isozymes in pancreatic β cells and their physiologic relevance in the regulation of insulin secretion have not been studied so far. The present study showed that PLC‐β1 was crucial for β‐cell function by generation of each PLC‐β conditional knockout mouse. Mice lacking PLC‐β1 in β cells exhibited a marked defect in GSIS, leading to glucose intolerance. In ex vivo studies, the secreted insulin level and Ca 2+ response in Plcb1 f/f ; pancreas/duodenum homeobox protein 1 ( Pdx1 )‐Cre recombinase‐estrogen receptor T2 ( CreERt2 ) islets was lower than those in the Plcb1 f/f islets under the high‐glucose condition. PLC‐β1 led to potentiate insulin secretion via stimulation of particular Gq ‐protein–coupled receptors. Plcb1 f/f ; Pdx1‐CreERt2 mice fed a high‐fat diet developed more severe glucose intolerance because of a defect in insulin secretion. The present study identified PLC‐β1 as an important molecule that regulates β cell insulin secretion and can be considered a candidate for therapeutic intervention in diabetes mellitus.—Hwang, H.‐J., Yang, Y. R., Kim, H. Y., Choi, Y., Park, K.‐S., Lee, H., Ma, J. S., Yamamoto, M., Kim, J., Chae, Y. C., Choi, J. H., Coceo, L., Berggren, P.‐O., Jang, H.‐J., Suh, P.‐G. Phospholipase Cβ1 potentiates glucose‐stimulated insulin secretion. FASEB J. 33, 10668–10679 (2019). www.fasebj.org